Средства обеспечения компьютеризованого контроля характеристик электронных систем - Нехрест, В. В.; Карнаушенко, В. П. (ХНУРЕ, 2017)
Currently, subject to stringent time requirements on specific issues of science and technology. This is due to high competition in the market for new technologies and the pace of technological development. To speed up the cycle of research, there are several ways: increase the number of researchers, that is not economically viable and is not always justified, and automate routine operations with intelligent systems for collecting and processing information. Such systems typically include a sensor signal, power normalization signal, information processing apparatus and the formation of the control actions. Such system is characterized by a response time to changes in the signal, the degree of distortion of data, specialization.
Keywords: Контроль характеристик электронных систем